Meningkatkan Aksebilitas dan Kemudahan Pendaftaran Siswa Baru dengan Sistem Informasi Berbasis Web - Akmal Hidayat; Astri Maulina; Dinda Nisrina Adisafira; Hijir Ismail; Muh. Fadlan Amrullah (Indonesian Technology and Education Journal, 2024)
Registration of new students is a very important process for every school in order to get the best students to enter and study at that institution. A smooth and easy enrollment process is key to enhancing the experience of prospective students and improving the efficiency of school administration. Thus, researchers designed a system that helps prospective new students in registering, as well as processing new student data that will be stored safely into the system's database. In designing this information system, the waterfall model method is used, with several stages such as requirements analysis, system design, also applying the OOAD method or Object Based Analysis. This research produces a web-based new student registration information system that is accessed in real-time without being limited by space and time. This system is tested using the blackbox and whitebox methods, by testing the features contained in the designed system which focuses on functions and logic that can run according to the results expected by the researcher.